Preparation method of three-dimensional rod-like flower cluster CdS QDs (at) ZnS / ZnO composite photocatalyst

The preparation of CdS QDs@ZnS/ZnO composite photocatalysts by microwave-assisted hydrothermal method solves the problem of low photocatalytic efficiency of ZnO, and achieves efficient degradation of organic pollutants and photolysis of water to produce hydrogen, which significantly improves solar energy utilization.

CN119386897APending Publication Date: 2025-02-07QIQIHAR UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411596260.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The photocatalytic efficiency of ZnO photocatalyst is low and can only be activated by ultraviolet light, and the solar energy utilization rate is low.

Method used

CdS QDs@ZnS/ZnO composite photocatalysts were prepared by microwave-assisted hydrothermal method, and CdS QDs was used to broaden the light absorption range to form a three-dimensional flower cluster-shaped composite catalyst to improve the separation efficiency of photogenerated carriers.

Benefits of technology

Efficient degradation of organic pollutants and photolysis of water hydrogen production were achieved. The degradation efficiency of rhodamine B in simulated sunlight reached 91.3%, the hydrogen production was significantly improved, and the photocatalytic activity was stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386897A_ABST
    Figure CN119386897A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a three-dimensional flower-cluster-shaped CdS QDs (at) ZnS / ZnO composite photocatalyst, belongs to the field of preparation of photocatalytic materials, and aims to solve the problem of relatively low photocatalytic efficiency. The preparation method comprises the following steps: 1, preparing zinc oxide: dissolving Zn (CH3COO) 2.2 H2O in deionized water, stirring until Zn (CH3COO) 2.2 H2O is completely dissolved, adding NaOH, stirring to form an emulsion, transferring the mixed emulsion into a polytetrafluoroethylene reaction kettle, and treating at 160 DEG C for 10 hours; 2, preparation of cadmium sulfide quantum dots (CdS QDs): dropwise adding thioacetamide (TAA) into a Cd (NO3) 2.4 H2O aqueous solution, continuously stirring and dropwise adding a NaOH solution, adjusting the pH value of the solution to 10.5, then adding a Na2S solution, stirring at 65 DEG C for 1 h, cooling to room temperature, and aging for 24 h; and 3, dissolving Zn (CH3COO) 2.2 H2O and TAA in deionized water, adding ZnO powder, adding CdS QDs, and carrying out rapid stirring. Putting into a microwave reaction instrument, reacting at 160 DEG C for 45 minutes, washing and drying. The three-dimensional flower-cluster-shaped CdS QDs (at) ZnS / ZnO composite photocatalyst is prepared through a microwave-assisted hydrothermal method, and the photocatalytic oxidation performance is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalytic degradation and photolysis of water to produce hydrogen technical material preparation, and relates to a preparation method of a CdS QDs@ZnS / ZnO composite photocatalyst. Background Art

[0002] With the rapid development of industrialization and urbanization today, a large amount of toxic and harmful organic pollutants are released into the environment, such as dyes and antibiotics, leading to problems such as environmental pollution and global energy shortage.

[0003] Metal oxide semiconductors, as popular photocatalysts, have outstanding performance in treating wastewater containing organic pollutants, and have achieved environmental remediation in today's energy shortage and severe environmental pollution. Zinc oxide (ZnO) is a wide bandgap direct bandgap semiconductor. As a traditional photocatalyst, ZnO has good chemical stability, but can only be activated by ultraviolet light, and the utilization rate of solar energy is low. Therefore, the development of efficient solar light-responsive photocatalysts has become an important task. The arrangement of ZnO atoms or ions is not completely regular, and there are crystal defects. In the case of sufficient oxygen source, zinc defects are dominant, while in the case of sufficient zinc source, oxygen vacancies are more likely to appear. At the same time, abundant oxygen vacancies contribute to the separation of photogenerated electrons and holes, which is an important way to improve photocatalytic performance. Zinc sulfide (ZnS) is a wide bandgap catalyst that can only absorb ultraviolet light, so the use of pure ZnS photocatalysts is limited. ZnS has excellent semiconductor properties and outstanding performance as a visible light photocatalyst, which can decompose water and degrade organic pollutants. Cadmium sulfide (CdS), a narrow bandgap material, is highly active under visible light. As a new surface modification method, quantum dots are widely used in surface loading modification of photocatalysts. CdS quantum dots (CdS QDs) are considered to be a promising photocatalytic material due to their small size (<10 nm), high electron mobility and quantum effect. The combination of narrow-bandgap CdS and wide-bandgap ZnO and ZnS can construct energy-level matching composite materials, making it easier to achieve photocatalytic water splitting to produce hydrogen. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of low photocatalytic efficiency of ZnO and to provide a method for preparing a CdS QDs@ZnS / ZnO composite photocatalyst.

[0005] The preparation method of the CdS QDs@ZnS / ZnO composite photocatalyst of the present invention is implemented by the following steps:

[0006] 1. Preparation of ZnO precursor: Dissolve 0.878±0.0005 g Zn(CH3COO)2·2H2O in 60 mL deionized water, stir until completely dissolved, add 2.4±0.0005 g NaOH and stir to form an emulsion, then transfer the mixed emulsion to a polytetrafluoroethylene reactor and treat at 160 °C for 10 h. After the reaction is completed, wash with deionized water and anhydrous ethanol several times, and collect the white ZnO product by centrifugation;

[0007] 2. Preparation of precursor CdS QDs: First, thioacetamide (TAA) was dripped into 200 mL Cd(NO3)2·4H2O aqueous solution and stirred continuously. After 30 min, 1% Cd(NO3)2·4H2O was added dropwise to the above solution under continuous stirring. The NaOH solution was added to adjust the pH of the solution to 10.5, and then 10 mL of Na2S solution was added. The reaction was stirred at 65 °C for 1 hour, cooled to room temperature, aged for 24 hours, and a yellow CdS precipitate was formed. The lower precipitate was obtained by centrifugation, washed with deionized water and ethanol, and dried at room temperature;

[0008] 3. Microwave-assisted hydrothermal synthesis: 0.08±0.0005 g Zn(CH3COO)2·2H2O and 0.08±0.0005 g thioacetamide (TAA) were dissolved in 40 mL deionized water, stirred until completely dissolved, and 0.2±0.0005 g pre-prepared ZnO powder was added and continued to stir to form solution A. Similarly, a certain mass of pre-prepared CdS QDs was dissolved in 10 mL of deionized water, and ultrasonically dispersed to form solution B. Subsequently, solution B was mixed with solution A and stirred rapidly for a certain period of time. Finally, the mixed solution was transferred to a PTFE standard reactor, placed in a microwave reactor at 160 ° C (slope of 30 min) for microwave reaction for 45 min (power 300 W), cooled to room temperature, washed and vacuum dried for 24 h to obtain CdS QDs@ZnS / ZnO composite photocatalytic material;

[0009] The molar mass ratio of ZnS and ZnO pre-prepared in step 3 is 1:2.

[0010] Principle of the present invention:

[0011] The present invention uses rod-shaped ZnO as a precursor and adopts a microwave-assisted hydrothermal method to prepare a CdS QDs@ZnS / ZnO composite photocatalyst with full-spectrum photocatalytic activity for degrading organic pollutants. On the one hand, the introduction of CdS QDs further broadens the light absorption range of ZnS / ZnO and improves the utilization rate of light; on the other hand, the three-dimensional flower cluster-shaped The composite catalyst increases the number of active sites on its surface, which is beneficial to increasing the contact area with organic pollutants; on the other hand, a close contact heterojunction is formed between cadmium quantum dots, ZnS and ZnO, which improves the separation efficiency of photogenerated carriers, thereby effectively improving the photocatalytic activity of the composite material.

[0012] Beneficial effects of the present invention:

[0013] 1. The present invention prepares a CdS QDs@ZnS / ZnO composite photocatalyst by a microwave-assisted hydrothermal method. The composite material is composed of hexagonal wurtzite phase ZnO, cubic phase ZnS and cubic phase CdS quantum dots. The composite photocatalyst CdS QDs@ZnS / ZnO maintains a good flower cluster structure. Compared with direct photolysis and monomer photocatalysis, the composite photocatalyst has a better photodegradation effect on the organic pollutant Rhodamine B (RhB) under simulated sunlight. After 120 minutes of simulated sunlight irradiation, the CdSQDs@ZnS / ZnO composite material exhibits a degradation efficiency of up to 91.3%. The sacrificial agent solution has a high hydrogen production under the irradiation of 300 W xenon lamp. The composite photocatalyst The amount of hydrogen evolution reached 6185.12 , which is 67.4 times that of monomer ZnO, and its photocatalytic activity remains stable after three cycles, which fully demonstrates the excellent hydrogen production performance of the prepared catalyst;

[0014] Second, the preparation process is simple, easy to operate, has good repeatability and low cost. At the same time, the reaction conditions are mild and carried out at room temperature and pressure. The purity and yield of the composite catalyst are high. The preparation process not only saves the use of chemicals, but also reduces the harm to the environment caused by excessive organic pollutants in water, realizes the concept of "green chemistry", and is easy for industrial application;

[0015] 3. The present invention also provides a new path for the treatment of dye wastewater using photocatalysts represented by CdS QDs@ZnS / ZnO heterojunction, which has the advantage of high treatment efficiency and is conducive to the transformation of the technology from laboratory research to large-scale practical application, which can effectively repair the environment and create certain economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the XRD spectrum of the CdS QDs@ZnS / ZnO composite photocatalytic particles obtained in Example;

[0017] Figure 2 is a SEM surface morphology image of the CdS QDs@ZnS / ZnO composite photocatalytic particles obtained in Example;

[0018] Figure 3 is a TEM transmission image of the CdS QDs photocatalytic particles obtained in Example;

[0019] Figure 4 is a HRTEM image of the CdS QDs@ZnS / ZnO composite photocatalytic particles obtained in Example;

[0020] Figure 5 It is the reaction rate diagram of direct degradation, ZnO, ZnS / ZnO and CdS QDs@ZnS / ZnO with different ratios of simulated sunlight catalytic degradation of Rhodamine B;

[0021] Figure 6 It is the reaction rate diagram of direct degradation, UV-photocatalytic degradation of Rhodamine B by ZnO, ZnS / ZnO and CdS QDs@ZnS / ZnO with different ratios;

[0022] Figure 7 It is the kinetic result diagram of the UV-photocatalytic degradation of Rhodamine B by direct degradation, ZnO, ZnS / ZnO and different proportions of CdS QDs@ZnS / ZnO;

[0023] Figure 8 This is a diagram showing the results of photocatalytic water splitting and hydrogen production in Na2S-Na2SO3 solution using P25, ZnO, ZnS / ZnO and three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalysts. DETAILED DESCRIPTION

[0024] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0025] Specific implementation method 1: The preparation method of CdS QDs@ZnS / ZnO composite photocatalytic particles in this implementation method is implemented according to the following steps:

[0026] 1. Preparation of ZnO precursor: Dissolve 0.878±0.0005 g Zn(CH3COO)2 in 60 mL deionized water, stir until completely dissolved, add 2.4±0.0005 g NaOH and stir to form an emulsion, then transfer the mixed emulsion to a polytetrafluoroethylene reactor and treat at 160 °C for 10 h. After the reaction is completed, wash with deionized water and anhydrous ethanol several times, and collect the white ZnO product by centrifugation;

[0027] 2. Preparation of precursor CdS QDs: First, thioglycolic acid was dripped into 200 mL Cd(NO3)2·4H2O aqueous solution and stirred continuously. After 30 min, 1% The NaOH solution was added to adjust the pH of the solution to 10.5, and then 10 mL of Na2S solution was added. The reaction was stirred at 65 °C for 1 hour, cooled to room temperature, aged for 24 hours, and a yellow CdS precipitate was formed. The lower precipitate was obtained by centrifugation, washed with deionized water and ethanol, and dried at room temperature;

[0028] 3. Microwave-assisted hydrothermal synthesis: 0.08±0.0005 g Zn(CH3COO)2 and 0.08±0.0005 g TAA were dissolved in 40 mL deionized water, stirred until completely dissolved, and 0.2±0.0005 g pre-prepared ZnO powder was added and continued to stir to form solution A. Similarly, a certain mass of pre-prepared CdS QDs was dissolved in 10 mL of deionized water, and ultrasonically dispersed to form solution B. Subsequently, solution B was mixed with solution A and stirred rapidly for a certain period of time. Finally, the mixed solution was transferred to a PTFE standard reactor, placed in a microwave reactor at 160 ° C (slope of 30 min) for microwave reaction for 45 min (power 300 W), cooled to room temperature, washed and vacuum dried for 24 h, and CdS QDs@ZnS / ZnO composite photocatalytic material was obtained; wherein the molar mass ratio of ZnS and ZnO pre-prepared in step 3 was 1:2.

[0029] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the average particle size of the CdS QDs powder in step 1 is 2 to 5 nm.

[0030] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the magnetic stirring time in step one is 40 to 50 minutes.

[0031] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the stirring speed in step 1 is 290 r / min to 310 r / min. The other steps are the same as those in specific implementation methods 1 to 3.

[0032] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the Cd(NO3)2·4H2O solution described in step 1 is 0.0875 , Na2S solution is 1 , the other steps are the same as those in Specific Embodiments 1 to 4.

[0033] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the microwave reaction temperature in step 1 is 160° C., the reaction time is 45 min, and the power is 300 W. The other steps are the same as specific implementation methods 1 to 5.

[0034] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 1, the reaction product is washed 3 to 5 times with deionized water and anhydrous ethanol respectively, and then kept at 55°C to 65°C for 45 h to 50 h to obtain a CdS QDs@ZnS / ZnO composite photocatalyst. The other steps are the same as those of specific embodiments 1 to 6.

[0035] The three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalyst is described in detail below with reference to the accompanying drawings.

[0036] 1. Surface morphology and microstructure

[0037] The three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalyst prepared by microwave-assisted hydrothermal method is composed of hexagonal wurtzite ZnO, cubic ZnS and cubic CdS QDs. Figure 1 The crystal phase composition and crystal structure of the composite material can be observed. Figure 2 It can be clearly observed that the sample presents a three-dimensional flower cluster morphology composed of hexahedral rods. Figure 3 Transmission electron microscope image of CdS QDs. Figure 4 This is a HRTEM image of a three-dimensional flower cluster CdS QDs@ZnS / ZnO sample. From the image, we can see the (101) crystal plane of ZnO, the (111) crystal plane of ZnS and the (101) crystal plane of CdS QDs.

[0038] 2. Photocatalytic performance determination

[0039] The photocatalytic experiments on direct photodegradation, monomeric ZnO, binary ZnS / ZnO, and three-dimensional flower cluster CdS QDs@ZnS / ZnO were carried out to degrade the organic pollutant Rhodamine B and to produce hydrogen through photolysis of water.

[0040] Degradation of organic pollutants Rhodamine B Figure 5 , Figure 6 The results show that the three-dimensional flower cluster CdS QDs@ZnS / ZnO composite material exhibits the highest photocatalytic activity for the degradation of Rhodamine B under simulated sunlight and ultraviolet light, far exceeding that of monomer ZnO. In addition, the effects of different samples on the degradation rate of Rhodamine B are shown in Figure 7 According to the experimental data, according to the formula Calculate, where C t is the concentration of the dye at time t ( ), C0 is the initial concentration of dye ( ), k is the rate constant ( ), b is the intercept. Figure 7 visible, It is basically linear with the reaction time t, which indicates that the degradation of the dye Rhodamine B follows pseudo-first-order reaction kinetics. The results of hydrogen production from photolysis of water P25, ZnO, ZnS / ZnO and three-dimensional flower cluster CdS QDs@ZnS / ZnO in a solution with Na2S+Na2SO3 as sacrificial agent are shown in Figure 8 The results show that the three-dimensional flower cluster CdS QDs@ZnS / ZnO composite material has the best hydrogen production ability.

Claims

1. A method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalyst, characterized in that This method is implemented in the following steps:

1. Preparation of ZnO precursor: Dissolve 0.878±0.0005 g Zn(CH3COO)2 in 60 mL deionized water, stir until completely dissolved, add 2.4±0.0005 g NaOH and stir to form an emulsion, then transfer the mixed emulsion to a polytetrafluoroethylene reactor and treat at 160 °C for 10 h. After the reaction is completed, wash with deionized water and anhydrous ethanol several times, and collect the white product ZnO by centrifugation; Preparation of the precursor cadmium sulfide quantum dots (CdS QDs): First, thioglycolic acid was dripped into 200 mL Cd(NO3)2·4H2O aqueous solution and stirred continuously. After 30 min, 1 mol·L -1 NaOH solution was added to adjust the pH of the solution to 10.5, and then 10 mL of Na2S solution was added. The reaction was stirred at 65 °C for 1 hour, cooled to room temperature, aged for 24 hours, and a yellow precipitate of cadmium sulfide was formed. The lower precipitate was obtained by centrifugation, washed with deionized water and ethanol, and dried at room temperature; 3. Microwave-assisted hydrothermal synthesis: Dissolve 0.08±0.0005 g Zn(CH3COO)2 and 0.08±0.0005 g TAA in 40 mL deionized water, stir until completely dissolved, add 0.2±0.0005 g pre-prepared ZnO powder and continue stirring to form solution A. Similarly, a certain mass of pre-prepared CdS QDs was dissolved in 10 mL of deionized water, and ultrasonically dispersed to form solution B. Subsequently, solution B was mixed with solution A and stirred rapidly for a certain period of time. Finally, the mixed solution was transferred to a polytetrafluoroethylene reactor, placed in a microwave reactor at 160 ° C (slope of 30 min) for microwave reaction for 45 min (power 300 W), cooled to room temperature, washed and vacuum dried for 24 h to obtain CdS QDs@ZnS / ZnO composite photocatalytic material; The molar mass ratio of ZnS and ZnO pre-prepared in step 3 is 1:

2.

2. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that In step 1, ZnO grows into a three-dimensional flower cluster in the shape of hexagonal rods.

3. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that The magnetic stirring time in step 1 is 40 to 50 min in total.

4. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that Step 1: react at 160 °C for 10 h.

5. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that Step 2: react at 65 °C for 1 h.

6. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that In step 2, the particle size of CdS QDs is 2 nm to 5 nm.

7. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that The stirring speed in step 3 is 290 r / min~310 r / min.

8. The method for preparing a three-dimensional rod-shaped flower cluster CdS QDs@ZnS / ZnO composite photocatalytic particle according to claim 1, characterized in that In step 3, the microwave reaction temperature was 160 °C for 45 min (power was 300 W).

Citation Information

Cited By

  • Preparation method of composite photocatalyst graphene oxide / BiVO4

    CN112691656A

  • Preparation method of composite photocatalyst graphene oxide / biVO4

    CN112691656B